An investigation into the importance of rhythmic and melodic variation for Brahm's development sections, with special reference to his four symphonies - Schoeman, Delene Letitia (Rhodes University, Faculty of Humanities, Department of Music, 1966)
"Variation is one of the oldest and most elemental types of music, beloved and practised by all musicians since the early lute and keyboard composers." The principle of the variation is that of "variety within unity, secured by the reproduction of limited musical material in changing aspects and is fundamental to composition." Typical instances are the use of fugal themes in changing combinations and with changing counter-material; continuous sequential expansion of a single motif in the baroque sonata or suite; the symphonic development in classical sonata form; ornamentation, compression, extension or elaboration of recapitulated sections. Intro., p. 1.
Keywords: Brahms, Johannes, 1833-1897 -- Symphonies; Variations -- History and criticism